1256. Contemporary Evaluation of Racial/Ethnic Disparities in Survival and Disease Progression among People with HIV in the US Midwest - Khazanchi, Rohan (Open Forum Infect Dis, 2019)
BACKGROUND: Combating HIV-related disparities is a major goal of the 2020 National HIV/AIDS Strategy. However, research on HIV disparities has primarily been conducted in urban settings. A 1997–2007 study of people with HIV (PWH) at our clinic noted significantly increased mortality among high-risk non-Hispanic (NH) Black PWH (73%) compared with NH Whites (88%). This study evaluated demographic disparities in survival and disease progression in a large Midwest clinical cohort. METHODS: We retrospectively reviewed records of 1,396 PWH receiving treatment at an HIV Clinic in Omaha, Nebraska from 2012 through 2017. We included patients over 19 years old with diagnosed HIV, a minimum of two visits, and no lapse in care >2 years. Patients were stratified into low-risk (CD4 >100 cells/mm(3) and HIV viral load <250,000 copies/mL) and high-risk (all others) groups. Cox proportional hazard models and Kaplan–Meier curves with log-rank tests compared patient demographics and mortality. Generalized estimating equations modeled change in CD4 count over time. RESULTS: No significant difference in mortality was noted across race/ethnicity categories (P = 0.286). Several clinical and demographic characteristics, including CD4 counts <500 cells/mm(3), were significantly associated with increased mortality (Figure 1). Compared with NH Whites, mean CD4 counts (Figure 2) were significantly lower for NH Blacks (P = 0.001), Hispanics (P = 0.006), and Others (P = 0.013). High-risk status was associated with mortality (P < 0.001), but no significant differences in mortality were noted across race/ethnicity categories after stratifying for patient risk status (Figures 3 and 4). CONCLUSION: Significant racial/ethnic disparities in HIV disease progression among PWH at a Midwest HIV Clinic persist. However, in contrast to the 1997–2007 study, disparities in survival were not observed among high-risk PWH. As our patient demographics are essentially the same, the reduction of this disparity suggests needed investigation of whether these changes are the result of better antiretroviral efficacy or if social determinants of health in the region have improved. Systems-level interventions are needed to ensure all PWH benefit from continuing advances in HIV research and care. [Image: see text] [Image: see text] [Image: see text] [Image: see text] DISCLOSURES: All authors: No reported disclosures.